Manufacturing Consent for Vaccine Mandates: A Comparative Case Study of Communication Campaigns in France and Australia - Attwell, Katie; Ward, Jeremy K.; Tomkinson, Sian (Frontiers in Communication, 2021)
Governments making childhood vaccination more mandatory is controversial, and can be met with pushback from the public. Hence such policies may be accompanied by some form of communication to manufacture consent for either vaccination, mandatory vaccination policies, or both. This paper engages in case studies of two countries which recently made vaccination more mandatory and accompanied this policy change with concerted communication campaigns. It examines the French and Australian government's new mandatory vaccination regimes, the communication strategies undertaken to manufacture consent for them, and the complex ways these policies interact. The analytical focus is the content of the websites at the centre of the communications campaigns, “Vaccination-Info-Service” and “Get the Facts”, as well as relevant academic articles, government press releases, documents and reports, and key informant interviews conducted in both countries. We report three key findings. First, we demonstrate how both countries’ governance strategies intertwine persuasion with coercion in complex ways. Second, we examine how each country’s website reflects local constructions of under-vaccination, especially regarding social groups and motivations. Third, we consider their vastly different communication styles and how these reflect alternative ways of constructing the public as well as differences in the use of communication expertise in the websites’ production. These factors produce different tactics regarding manufacturing consent for vaccination and for vaccine mandates. We conclude that manufacturing consent for vaccination is a laudable exercise, but find that the involvement of numerous actors and institutions results in various interests, objectives, and conceptions of what drives audience reception, resulting in divergent strategies. This is particularly the case when it comes to manufacturing consent for vaccine mandates themselves; a more complex task that relies on strong understandings of community, knowledge, and effective channels of state power.